(untitled) (CAHIERS MAGELLANES-NS, 2024)
Job Campus represents a groundbreaking web application tailored specifically for college students, aiming to revolutionize the landscape of career exploration and job placement. Powered by the fusion of Spring Boot and React.js technologies, this platform serves as a comprehensive career navigator, providing students with invaluable insights into the companies recruiting from their colleges. Job Campus is a platform that helps students bridge the gap between academic learning and real-world career opportunities. The platform uses historical student data to provide students with a holistic view of job roles, salary packages, and geographic preferences. This data-driven approach helps students make informed decisions about their professional trajectories. Job Campus was founded in response to the pressing need to help students make informed decisions about their careers. The platform's founders recognized that the traditional job search process is often overwhelming and confusing for students. They also realized that students often lack the information they need to make informed decisions about their careers. Job Campus addresses these challenges by providing students with a comprehensive view of the job market. The platform's database includes information on job roles, salary packages, and geographic preferences. This information is collected from a variety of sources, including job boards, company websites, and government agencies. .